Les représentations sociales pour cerner l’évolution des conceptions de la forêt québécoise : une analyse autour du documentaire L’erreur boréale - Isabelle Paré (VertigO)
The multiplicity of ways to apprehend nature and the environment necessarily transpose to the understanding of forests. Nevertheless, understanding how people conceive the latter is more complex than it appears. In this multiple, flexible and social reality, forests convey different meanings, experiences, and knowledge. As controversies over the management of public forests are frequent, the complexities of forests understanding must be approached with nuances. This study examines in what ways forest is conceptualized in public discourses, using the analytical tools proposed by the theory of social representations (SR). It also sheds light on how a controversy, the case of the documentary L’erreur boréale (Forest Alert), fuelled the transformation of these conceptions. Using a sequential mixed method design combining a similarity analysis to a thematic content analysis, we uncover social representations of forest as they were conveyed in the daily newspaper La Tribune, both before and after the broadcasting of L’erreur boréale. Divergent conceptions of forest were found. Before the release of the film, the analysis revealed a single SR : the generous forest. The controversy has led to the emergence and transformation of four SR : the defenseless forest, the tough but generous forest, the threatened forest and the abstract forest.